Historical Volcanism and the State of Stress in the East African Rift System - Wadge, G.; Biggs, J.; Lloyd, R.; Kendall, J.-M. (Frontiers in Earth Science, 2016)
Crustal extension at the East African Rift System (EARS) should, as a tectonic ideal, involve a stress field in which the direction of minimum horizontal stress is perpendicular to the rift. A volcano in such a setting should produce dykes and fissures parallel to the rift. How closely do the volcanoes of the EARS follow this? We answer this question by studying the 21 volcanoes that have erupted historically (since about 1800) and find that 7 match the (approximate) geometrical ideal. At the other 14 volcanoes the orientation of the eruptive fissures/dykes and/or the axes of the host rift segments are oblique to the ideal values. To explain the eruptions at these volcanoes we invoke local (non-plate tectonic) variations of the stress field caused by: crustal heterogeneities and anisotropies (dominated by NW structures in the Protoerozoic basement), transfer zone tectonics at the ends of offset rift segments, gravitational loading by the volcanic edifice (typically those with 1-2 km relief) and magmatic pressure in central reservoirs. We find that the more oblique volcanoes tend to have large edifices, large eruptive volumes and evolved and mixed magmas capable of explosive behaviour. Nine of the volcanoes have calderas of varying ellipticity, 6 of which are large, reservoir-collapse types mainly elongated across rift (e.g. Kone) and 3 are smaller, elongated parallel to the rift and contain active lava lakes (e.g. Erta Ale), suggesting different mechanisms of formation and stress fields. Nyamuragira is the only EARS volcano with enough sufficiently well-documented eruptions to infer its long-term dynamic behaviour. Eruptions within 7 km of the volcano are of relatively short duration (<100 days), but eruptions with more distal fissures tend to have greater obliquity and longer durations, indicating a changing stress field away from the volcano. There were major changes in long-term magma extrusion rates in 1977 (and perhaps in 2002) due to major along-rift dyking events that effectively changed the Nyamuragira stress field and the intrusion/extrusion ratios of eruptions.